H3K4me1 Distribution Predicts Transcription State and Poising at Promoters - Bae, Sunhee; Lesch, Bluma J. (Frontiers in Cell and Developmental Biology, 2020)
Monomethylation on lysine 4 of histone H3 (H3K4me1) is commonly associated with promoter-distal enhancers, but H3K4me1 is also present at promoter regions. To assess a possible role for H3K4me1 in dictating gene regulatory states at promoters, we examined H3K4me1 peak density around promoters in human and mouse germ cells using an analytic strategy that allowed us to assess relationships between different epigenetic marks on a promoter-by-promoter basis. We found that H3K4me1 exhibits either a bimodal pattern at active promoters, where it flanks H3K4me3, or a unimodal pattern at poised promoters, where it coincides with both H3K4me3 and H3K27me3. This pattern is correlated with gene expression level, but is more strongly linked to the poised chromatin state than to transcriptional activity. We propose that H3K4me1 is a key feature of poised epigenetic state, and suggest possible roles for this mark in epigenetic memory.